2011
DOI: 10.1590/s0100-204x2011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Meta-análise da digestibilidade ileal de aminoácidos e minerais em suínos alimentados com dietas contendo enzimas

Abstract: Resumo -O objetivo deste trabalho foi avaliar, por meio da meta-análise, o efeito da fitase e da xilanase sobre a digestibilidade ileal aparente (DIa) de aminoácidos, cálcio e fósforo, em suínos em fase de crescimento. A base de dados consistiu de 21 artigos publicados entre 1998 e 2009, no total de 82 tratamentos e 644 suínos. A meta-análise foi realizada por análise gráfica, de correlação, de variância-covariância. As concentrações de fósforo fítico e as frações fibra em detergente neutro, fibra em detergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Protein utilization and amino acid absorption may also be influenced by dietary phytic acid levels (Lehnen et al, 2011;Walk et al, 2012). These authors observed that phytic acid is a potent chelating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Protein utilization and amino acid absorption may also be influenced by dietary phytic acid levels (Lehnen et al, 2011;Walk et al, 2012). These authors observed that phytic acid is a potent chelating agent.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to increase in the enzyme activity, necessary for growth by causing better feed utilization in the gastrointestinal tract and released minerals for growth (Rajpoot 2009). Protein utilization and amino acid absorption may also be influenced by dietary phytic acid (Lehnen et al 2011, Walk et al 2012, 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary Calcium and Phosphorus increased relative liver and heart weights. The bones of broilers fed phytase-supplemented diets presented higher ash content (Lehnen et al 2011, Walk et al 2014.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a growing interest in the use of meta-analysis in areas related to animal production and veterinary sciences as an essential tool for synthesizing computed results from multiple studies, particularly in those in which the effect is not readily detectable and the sample smaller . In addition, a large number of studies have shown the application of this technique (Sanches et al, 2007, Averos et al, 2010Lehnen et al, 2011;Carvalho et al, 2011;Andreatta et al, 2012Andreatta et al, 2016). The use of meta-analysis in the animal environment makes it possible to obtain a larger sample by combining several studies already performed, allowing a more accurate response than that obtained in individual studies (Giannoti 2004).…”
Section: Introductionmentioning
confidence: 99%